GEOPOLITICAL RIVALRY BETWEEN RUSSIA AND NATO IN THE CONTEXT OF THE CRISIS IN RUSSIAN-UKRAINIAN RELATIONS - N. D. Shikher (Современная наука и инновации)
The question of the national idea of the Russian state at all times aroused genuine interest in the scientific community, in political circles, among philosophers and thinkers. It remains relevant in modern Russia, which has faced the globalization challenges of the secular world. At different social levels, the topic of the national idea provokes lively discussions and contributes to the emergence of a number of research projects. Purpose: to look at the choice of a national idea through the prism of Orthodox spiritual and moral values. Methodology: a comprehensive retrospective analysis of the history of the development of a national idea in Russia, a synthesis of modern views on this problem, a generalization of the data obtained, the formation of specific proposals for the future. As a result of a retrospective look at Russian history, it was revealed that it was the Orthodox factor that was the key in the choice of national ideas for the Russian state. This is due to the unique role of Orthodoxy in the life of society, which is difficult to overestimate. Despite the secular nature of modern Russia, Orthodoxy remains one of the most important self-identifiers of the Russian people. At the same time, in the scientific discourse, the topic of the study of the role of Ortho-doxy in the formation of the Russian national idea has a weak response, while in society and the state this problem is becoming increasingly relevant. In this regard, the author comes to the conclusion that it is necessary to attract the attention of the scientific community to this topic in order to develop a scientifically grounded basis for the formation of a high-quality and effective modern national idea based on Orthodox spiritual and moral values.